CO2 fixation and cultivation of Thermosynechococcus sp. CL-1 for the production of phycocyanin. (November 2022) - Narindri Rara Winayu, Birgitta; Hsueh, Hsin-Ta; Chu, Hsin
Graphical abstract: Highlights: TCL-1 presented 21.98 ± 1.52 mg/L/h CO2 fixation rate in 30 L flat panel photobioreactor. TCL-1 generated higher lipid content (49.91 %) than carbohydrate (24.22 %). Accumulated phycocyanin by TCL-1 was dominated by C-phycocyanin (98.10 ± 6.67 mg/g). Extraction with glucose provided heat and photo-damage protection to phycocyanin. Abstract: Cultivation of Cyanobacteria is preferable for CO2 fixation process due to its efficiency and production of beneficial byproducts like phycocyanin. In this study, Thermosynechococcus sp. CL-1 (TCL-1) was cultivated in a 30 L flat panel photobioreactor using a 3-fold-modified Fitzgerald medium with 113.2 mM dissolved inorganic carbon. The highest CO2 fixation rate of 21.98 ± 1.52 mg/L/h was followed by higher lipid content (49.91 % dry weight content or %dwc) than the generated carbohydrate (24.22 %dwc). TCL-1 also potentially produced phycocyanin that was dominated by C-phycocyanin (98.10 ± 6.67 mg/g) along with a lower amount of allophycocyanin and phycoerythrin under extraction using various types of solvent. Stability of phycocyanin extract was further examined during storage under various temperatures and light illuminations. Extraction with 36 % glucose solvent presented a protective effect to phycocyanin from heat and photo-damage which was proven by the kinetics study of phycocyanin degradation in this study.